Case report: Massive hepatocellular carcinoma with complete response to the non-surgical systematic treatment strategy - Li, Yun; Lai, Yanzhen; Luo, Xuqiang; Wu, Jian; Wu, Kunpeng; Ma, Haiqing (Frontiers in Oncology, 2024)
Background The five-year recurrence rate of hepatocellular carcinoma (HCC) remains as high as 70%. A complete clinical response has not been observed without surgical resection. Here, we report a rare case of clinical complete response and long-term survival in a patient with massive HCC receiving treatment with immunotherapy, anti-angiogenic therapy, and radiotherapy. Case description A 38-year-old woman presented to our hospital for abdominal pain that persisted for 3 months. She was diagnosed as Barcelona Clinic Liver Cancer(BCLC) stage A, with a Cancer of the Liver Italian Program (CLIP) score of 3, American Joint Committee on Cancer (AJCC) Tumor-Node-Metastasis (TNM) staging systems stage IB. She refused surgical resection and trans-arterial chemoembolization and accepted a non-invasive systematic treatment strategy involving immunotherapy, anti-angiogenic therapy, and radiotherapy. Her tumor burden decreased, and she experienced partial response before radiotherapy. Following radiotherapy, she experienced a complete clinical response and has been alive for more than 36 months after her initial presentation. She is currently alive. Conclusion A non-invasive systematic treatment strategy is a potential radical treatment option for patients with massive HCC.